SOSIALISASI SASARAN KESELAMATAN PASIEN SESUAI STARKES TERBARU DI RUMAH SAKIT PKU MUHAMMADIYAH KARTASURA - Burhannudin Ichsan; Dedhy Sastiyono (PT. Hasba Edukasi Mandiri, 2026)
PKU Muhammadiyah Kartasura Hospital has successfully implemented a number of patient safety target indicators. However, there are still shortcomings in several aspects, such as compliance with effective communication, ensuring the correct surgical site, correct actions, and appropriate patients for surgery. In addition, there is also a need to reduce the incidence of patient falls and improve nurses' knowledge, which is still considered lacking. The socialization of patient safety targets according to the health standards aims to increase the understanding and awareness of all healthcare workers regarding the importance of implementing patient safety in every service. The benefits of this activity are improving the quality and safety of patients and healthcare workers. The method used is socialization. Descriptive analysis of pretest and posttest scores showed abnormal data with a p-value of less than 0.05 in the Shapiro-Wilk test found in counseling participants. Furthermore, using the Wilcoxon test, a p-value of 0.014 was obtained, indicating a significant difference in employee knowledge at PKU Muhammadiyah Kartasura Hospital. This is due to the socialization process regarding the six patient safety targets at the hospital. Participants followed the event well, enthusiastically, and were able to understand the material provided. Participants were able to follow the discussion session well and practice good hand hygiene. Participants were enthusiastic in participating in the entire activity.